ELECTROPHORETIC STUDIES ON SEED PROTEINS OF VIABLE MUTANTS IN CAJANUS CAJAN (L.) MILLSP. - S. M. SANGLE (International Journal of Pharma and Bio Sciences, 2015)
In present investigation, the protein and polypeptide profiles of some pigeonpea mutants have been analyzed on Native and SDS-PAGE to understand genetic variability .Native PAGE gel analysis of viable mutants in variety BDN 708 showed considerable variations in protein profiling. SDS-PAGE analysis of viable mutants of pigeonpea revealed a wide range of protein polymorphism and variability with respect to number and mobility of polypeptide bands. Maximum bands could be found in early maturing mutant. Highest bands could be observed in xantha mutant followed by three seeded mutants in BSMR 853.